Acute aortic occlusion associated with COVID‐19: A rare complication of a not so rare disease - Ryan Lee; Robert Hsu (Journal of the American College of Emergency Physicians Open)
Abstract Recent literature has reported a high prevalence of thrombotic events associated with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) responsible for causing coronavirus disease 2019 (COVID‐19) infection. Although venous thromboembolism complications have been well studied, arterial thrombosis is less well described. Our aim is to describe acute aortoiliac occlusion (AAO), itself a rare condition, as a complication of COVID‐19 infection and review existing literature regarding its presentation and available treatment modalities. Over a 2‐week span in late 2021, 2 patients with recent COVID‐19 infection presented to our tertiary care hospital with AAO. Each case was treated with a multimodal therapeutic approach, including vascular interventional radiology guided thrombolysis, vascular surgical approach, and systemic anticoagulation. Although two separate primary approaches were taken, each resulted in high morbidity and death in both cases. Acute aortic occlusion is a rare disease associated with high morbidity and mortality. COVID‐19 has further been associated with arterial thromboembolic complications, including AAO, as presented here. More research is needed to identify patients at highest risk of developing arterial thromboembolic disease after COVID‐19 infection as well as to determine ideal therapeutic options in order to improve the exceedingly high morbidity and mortality associated with this complication.